Degenerative Mitral Valve Repair Restores Life Expectancy - Watt, Tessa M. F. (Ann Thorac Surg, 2019)
BACKGROUND: Mitral valve repair (MVr) for severe, degenerative mitral regurgitation (MR) is the gold standard, as medical management carries poor prognosis. However, despite clear benefit of MVr, many eligible patients are untreated. This study investigated whether MVr restores patients to normal life expectancy, at any age of operation, by comparing long-term survival of post-MVr patients to the life expectancy of the general United States (U.S.) population. METHODS: This retrospective study investigated 1011 patients with degenerative MR who underwent isolated MVr between 2003 and 2017. Parametric distribution analysis was applied to long-term post-MVr mortality data, and Weibull probability plots provided the best-fit distribution by Anderson-Darling Goodness-of-Fit testing. Confidence intervals of the estimated distribution were used to compare additional life expectancy post-MVr to the general U.S. population across multiple decades of life. Post-MVr patients were categorized by age into decade (range 20–89 years). RESULTS: The life expectancy of post-MVr patients matched the life expectancy of the general U.S. population at any age between 40–89. Lower-bound one-sided 95% confidence intervals for additional life expectancy were not significantly different from corresponding median additional life expectancy of the general population. There were very few deaths in the 20–39 year-old group limiting predictability, but survival also appeared normative. CONCLUSIONS: These findings suggest that degenerative MVr restores anticipated life expectancy to that of the general population, regardless of age. While our findings underscore the importance of repair for degenerative mitral disease, larger studies with longer-term follow-up are needed to reinforce this finding, particularly for younger patients.